Friedrich Schneider (1786-1853) (Berlin; L. W. Krause; Germany, 2020)
Lithographed portrait of the pianist, conductor, and composer Friedrich Schneider (1786-1853), who as soloist performed Beethoven's Fifth Piano Concerto, for the first time in Leipzig, on November 28, 1811.